THE EFFECTS OF STUDENTS PERSONALITY AND INTELEGENCY TOWARDS ENGLISH LEARNING MOTIVATION - Riska Riani; Muljani A Nurhadi (Universitas Indraprasta PGRI, 2018)
The purpose of this research is to analyze and test the truth of hypotesis about the effects of students personality and intelegency towards English learning motivation. Reseach method that used is survey with regression and correlation analysis, they are the effect of data show students personality and intelegency with data show English learning motivation. The data are gotten with instrument that is arranged by writer, that is measures things which are related with variables. The population of this research are the students of XI Level of SMAN at Aceh Baarat Daya Regency, and the number of sample as much as 53 students using simple random sampling. The result of hypotesis test is obtained conclusions are: There are significant simultaneously effects of students personality and intelegency towards English learning motivation, SMAN students of XI level at Aceh Barat Daya Regency. It is proven with sig score = 0,000 < 0,05 and Fcount = 12,736. There is a significat effect of students personality towards English learning motivation, SMAN students of XI level at Aceh Barat Daya Regency. It is proven with sig score = 0,014 < 0,05 and Tcount = 2.548. There is a significat effect of students intelegency towards English learning motivation, SMAN students of XI level at Aceh Barat Daya Regency. It is proven with sig score = 0,005 < 0,05 and Tcount = 2.937. Keywords: Students personality, Students intelegency, English learning motivation